Solving and analyzing DSGE models in the frequency domain - Alexander Meyer-Gohde (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
I provide a solution method in the frequency domain for multivariate linear rational expectations models. The method works with the generalized Schur decomposition, providing a numerical implementation of the underlying analytic function solution methods suitable for standard DSGE estimation and analysis procedures. This approach generalizes the time-domain restriction of autoregressive-moving average exogenous driving forces to arbitrary covariance stationary processes. Applied to the standard New Keynesian model, I find that a Bayesian analysis favors a single parameter log harmonic function of the lag operator over the usual AR(1) assumption as it generates humped shaped autocorrelation patterns more consistent with the data.
Keywords: C32; C62; C63; E17; E47; 330; DSGE; solution methods; spectral methods; Bayesian estimation; general exogenous processes